Pathways into Marriage: Cohabitation and the Domestic Division of Labor - Haynes, M; Hewitt, B; Baxter, Janeen (My University, 2010)
Does time spent in a cohabiting relationship prior to marriage lead to more egalitarian housework arrangements after marriage? Previous research has shown that housework patterns within cohabiting relationships are more egalitarian than in marital relationships. But do these patterns remain when couples marry? The findings from previous studies are mixed. This article uses three waves of data from the Household, Income and Labour Dynamics in Australia (HILDA) survey to examine changes in men’s and women’s time spent on housework as they transition into marriage. The results show that men’s housework hours remain stable regardless of life course pathway, and for women there is only minimal evidence that different pathways into marriage lead to different housework outcomes. The article concludes that the gender division of labor is developed well before the formation of a union and that the pathway to marriage has a relatively small effect on housework patterns after marriage.
Keywords: Relationships -- Marriage; Beliefs and Values; Beliefs and Values -- Housework; Relationships -- Cohabitation; Relationships; Lifestyle; Beliefs and Values; Relationships; Marriage; Housework; Cohabitation; Lifestyle